ANALISISSTRATEGI PENINGKATANDAYA SAING INDUSTRI MINYAK ATSIRI NILAM DENGAN PENDEKATANRANTAI NILAI DANKUALITASINDUSTRI (STUDIDIINDUSTRIMINYAK NILAMX, KULON PROGO) - , NOOR FITRI MARYANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Patchouli oil is one of the local products sold on the free market and traded internationally. Unstable price is a problem faced by domestic manufacturers, which caused 21 of 22 patchouli refiners in Kulonprogo switch to other commodities since 2009. In order to accommodate the price fluctuations, government has formulated an industrial priority development policy of essential oils with the Minister of Industry Regulation No. 136/MIND/ PER/2012 by implementing strategies to (1) increase and stabilize the price of essential oils, (2) shortening the marketing chain, (3) increasing the depth of the process chain, as well as (4) strengthening marketing capabilities especially for export. This study aims to determine the trade chain of patchouli oil in Kulonprogo District also the quality and competitiveness of industry X which is the object of research. In addition, analysis of the quality improvement aspects of the industry in order to improve competitiveness.Methods used in this study are value chain mapping, Policy Analysis Matrix for calculation of competitiveness, sensitivity analysis, and House of Quality to determine the priority of industrial improvement. The results showed that the producer has the largest profit by 33% in line with the risk faced by producer where profit can be increased in line with the reduction in the marketing chain and increased levels of Patchouli alcohol. In terms of competitiveness, industry X has been able to compete with similar producer as indicated by the value of Key Performace Indicators PCR at 0.84 and DRCR at 0.68 although the quality of the industry X for 7 of the 18 parameters under the quality of industry Y. Industry X reaches noncompetitive condition (PCR = 1) when patchouli oil prices decreased by 14%, patchouli leaf price increasedby 18.5%, and rising fuel prices by 437%. Improvement aspect that need to be done is improved purity of patchouli oil to increase competitiveness.